You are on page 1of 3

GITIMH3 94107 Polynomials Page 1

Introduction
22/01/99
For An Introduction of Polynomials See 3 unit Polynomials

Multiple Roots:
 Consider the polynomial P(x) = (x  b)r.Q(x) where Q(b)  0; so, x = b is a root of
multiplicity ‘r’ of the equation P(x) = 0

E.g. From the polynomial P(x) = (x  2)2(x2 + 5.x + 6), x= 2 is called a double
root of the equation P(x) = 0.

Theorem: If (x  a)r is a factor of P(x) = 0 [root of multiplicity r], then


(x  a)r  1 is a factor of P’(x) = 0 [root of multiplicity (r  1)], and
(x  a)r  2 is a factor of P’’(x) = 0 [root of multiplicity (r  2)], etc

Proof:
Let, P(x) = (x  b)r.Q(x) Where, Q(b)  0
 P’(x) = (x  b) .Q’(x) + Q(x).r(x  b)r  1
r

= (x  b)r  1.[(x  b).Q’(x) + Q(x).r]


= (x  b)r  1.S(x) Where, S(x) = (x  b)Q’(x) + Q(x).r
 x = b is a root of multiplicity (r  1) of the derived equation P’(x) = 0

Luke Cole Page 1


GITIMH3 94107 Polynomials Page 2

Complex Conjugate Roots of P(x):


 From 3 Unit Polynomials we know that a polynomial of degree ‘n’ has ‘n’ distinct
zeros.

E.g. (1) The polynomial P(x) = (x  2)3(x  3)(x + 1) has a degree 5, so there must
be 5 zeros. Zeros are: 2, 2, 2, 3,  1; here 2 is a zero of multiplicity 3

E.g. (2) The polynomial P(x) = x3  1 = (x  1)(x2 + x + 1) has a degree 3, so


 1  3 .i
there must be 3 zeros. Zeros are: 1,
2

 Observe that the complex zeros of the polynomial in e.g (2) are a conjugate pair.

Theorem: (a + i.b) & (a  i.b) are zeros of P(x) = 0, having real coefficients

Proof:
Let, Z = a + i.b be a complex zero of the polynomial P(x) with real coefficients
We use:
Z  a  i .b …(1)
2 2 …(2)
Z Z  a b
2 2 …(3)
Z .Z  a  b
To form the product:
   
x  Z  x  Z  x 2  Z  Z x  Z .Z …(4)
Sub (2) and (3) into (4):
 
x 2  Z  Z x  Z .Z  x 2  2.a.x  a 2  b 2
If P(x) is divided by x2  2.a.x + a2 + b2, the remainder must be of degree < 2.
Hence,P(x) = (x2  2.a.x + a2 + b2)Q(x) + m.x + n
= [x  (a + i.b)][x  (a  i.b)]Q(x) + m.x + n
Since, a + i.b is a zero of P(x), P(a + i.b) = 0. Substituting x = a + i.b, gives:
0 = 0 + m(a + i.b) + n
 0 = (a.m + n) + i.b.m
= 0 + 0.i
Comparing the real and imaginary parts separately, a.m + n = 0 and b.m = 0 and
hence m = and n = 0. (b  0)
Thus, P(x) = [x  (a + i.b)][x  (a  i.b)]Q(x)
Hence,P(a  i.b) = 0 i.e. a  i.b is also a zero of P(x)
 (a + i.b) & (a  i.b) are zeros of P(x) = 0, having real coefficients

Luke Cole Page 2


GITIMH3 94107 Polynomials Page 3

Relation Between Roots of P(x) = 0


22/01/99
 This is discussed on page 5 of 3 Unit Polynomials, however in general:

 a n1
Equation: x1 + x2 + … + xn =
an

a n 2
Equation: x1.x2 + x1.x3 + … =
an

…and so on

a0
x1.x2. … .xn =  1 
n
Equation:
an

Luke Cole Page 3